2020
DOI: 10.3389/fphys.2020.602027
|View full text |Cite
|
Sign up to set email alerts
|

Complexity-Based Decoding of the Coupling Among Heart Rate Variability (HRV) and Walking Path

Abstract: Walking is an everyday activity in our daily life. Because walking affects heart rate variability, in this research, for the first time, we analyzed the coupling among the alterations of the complexity of walking paths and heart rate. We benefited from the fractal theory and sample entropy to evaluate the influence of the complexity of paths on the complexity of heart rate variability (HRV) during walking. We calculated the fractal exponent and sample entropy of the R-R time series for nine participants who wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Consequently, the dynamics of spontaneous healthy brain activity are complex and contain information with fractal-like patterns that are self-similar over multiple scales of time 33 . In addition, Kamal and colleagues strengthened this concept by showing that healthy variable patterns are present in the brain and heart when participants walk on a fractal-like path 10,11 . Thus, consider additional biological rhythms will strengthen the multilevel dynamic interaction hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the dynamics of spontaneous healthy brain activity are complex and contain information with fractal-like patterns that are self-similar over multiple scales of time 33 . In addition, Kamal and colleagues strengthened this concept by showing that healthy variable patterns are present in the brain and heart when participants walk on a fractal-like path 10,11 . Thus, consider additional biological rhythms will strengthen the multilevel dynamic interaction hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrate similar patterns in their temporal structures. Recent preliminary research has showed such patterns to be present in the brain and heart when the individuals walked on a fractal-like path 10,11 and the brain when they finger-thumb tapped coordinating with an auditory fractal-like stimulus 12 . These results suggest an interaction between elements and systems at the temporal structure domain.…”
mentioning
confidence: 99%
“…However, the exact mechanism regulating HRV is not perfectly clear in every detail (Ernst, 2017;Rajendra Acharya et al, 2006). Some of recent developments in HRV have been mainly focused on nonlinear metrics such as variants of approximate entropy (ApEn) and sample entropy (SampEn) (Kamal et al, 2020;Lee & Choi, 2018;C. Liu et al, 2013;Sassi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…SampEn can be used to describe the regularity of temporal series, as it has lower values for time series with more frequent occurrence of sequences of similar consecutive values. Sample entropy method was used in physiology [51,52], geophysics [53], climatology [54], hydrology [30,34,35], and engineering [55].…”
Section: Sample Entropy (Sampen)mentioning
confidence: 99%